Creating appropriate training environments to improve technical, decision-making, and physical skills in field hockey - Timmerman, E.; Savelsbergh, G.; Farrow, D. (Research Quarterly for Exercise and Sport, 2019)
Purpose: The purpose of this study was to determine the influence of eight different small-sided games (SSG) on physical, technical, and decision-making demands of training environments in U14 field hockey. Methods: A total of 13 participants played eight different training games consisting of two 7.5-minute halves, where number of players (three per side or six per side) and/or field characteristics (normal game, cage hockey game, possession game, and two-goals game) was manipulated. Match performance was determined by using notational analysis, and physical demands were determined by using GPS analyses. Results: Findings revealed that lowering the number of players increased the number of technical actions performed per player and the physical demands of the SSG. Findings of the field characteristics manipulation revealed that the possession game forced players to control the ball more as a team, which resulted in more passes (+4.82 passes) and fewer dribbles (-1.48 dribbles) and tackles (-0.69 tackles) compared to the normal game. The two-goals game led to players scoring more goals (+0.61 goals) compared to the normal game, while the cage hockey game increased passing (+1.46 passes) and physical demands (+7.32 meters per minute) compared to the normal game. Conclusion: It can be concluded from these findings that coaches and trainers are able to promote a change in playing behavior, and in turn the development of skills, by manipulating specific constraints of the training environment.